Comparison of Rupture Risk of Intracranial Aneurysms Between Familial and Sporadic Patients. Issue 6 (June 2019) - Mensing, Liselore A.; Greving, Jacoba P.; Verhoeff, Tessa A.; Rinkel, Gabriel J.E.; Ruigrok, Ynte M.
Abstract : Background and Purpose: A much higher rupture rate for patients with familial intracranial aneurysms (IA) compared with patients with sporadic IA has been reported in a study with highly selected familial aneurysms using sporadic patients from other populations a controls. We aimed to validate these findings in a large independent series of Dutch patients with familial and sporadic IA. Methods: We conducted a secondary analysis of our institutional cohort of patients who were screened for IAs between 1994 and 2016. We assessed the incidence of aneurysmal subarachnoid hemorrhage between familial, defined as ≥2 affected first-degree relatives with aneurysmal subarachnoid hemorrhage and unruptured IA (UIA), and sporadic patients with UIA with Cox regression analysis. Results: We identified 62 familial IA patients with 91 UIA and 412 sporadic IA patients with 542 UIA. Despite familial aneurysms being smaller and more often located at low risk sites than sporadic IA, 3 familial patients had aneurysmal subarachnoid hemorrhage (0.77 ruptures per 100 aneurysm-years [95% CI, 0.20–2.09]) compared with 7 sporadic patients (0.51 ruptures per 100 aneurysm-years [95% CI, 0.22–1.01]). As compared to sporadic UIA, familial UIA seems to have a 3-fold higher risk of rupture (hazard ratio, 2.9 [95% CI, 0.6–14]). Conclusions: Our results suggest a slightly increased risk of aneurysm rupture for familial compared with sporadic IA, although we were not able to demonstrate this with statistical significance. However, the rupture risk seems less strongly increased than found in a previous study. Based on our results, we recommend to treat familial UIA more aggressively.